Differences between international recommendations on breastfeeding in the presence of HIV and the attitudes and counselling messages of health workers in Lilongwe, Malawi - Mtimuni Beatrice; Ahmed Yusuf; Tohill Beth; Nkhoma Jacqueline; Moses Agnes; Corneli Amy L; Bentley Margaret E; Ferguson Yvonne; Piwoz Ellen G; Jamieson Denise J; van der Horst Charles; Kazembe Peter (BMC, 2006)
Abstract Background To prevent postnatal transmission of HIV in settings where safe alternatives to breastfeeding are unavailable, the World Health Organization (WHO) recommends exclusive breastfeeding followed by early, rapid cessation of breastfeeding. Only limited data are available on the attitudes of health workers toward this recommendation and the impact of these attitudes on infant feeding counselling messages given to mothers. Methods As part of the Breastfeeding, Antiretroviral, and Nutrition (BAN) clinical trial, we carried out an in-depth qualitative study of the attitudes, beliefs, and counselling messages of 19 health workers in Lilongwe, Malawi. Results Although none of the workers had received formal training, several reported having counseled HIV-positive mothers about infant feeding. Health workers with counselling experience believed that HIV-infected mothers should breastfeed exclusively, rather than infant formula feed, citing poverty as the primary reason. Because of high levels of malnutrition, all the workers had concerns about early cessation of breastfeeding. Conclusion Important differences were observed between the WHO recommendations and the attitudes and practices of the health workers. Understanding these differences is important for designing effective interventions.